Recombinant protein production and purification of SiiD, SiiE and SiiF - Components of the SPI4-encoded type I secretion system from Salmonella Typhimurium - Klingl, Stefan; Kordes, Sina; Schmid, Benedikt; Gerlach, Roman; Hensel, Michael; Muller, Yves (Protein Expression and Purification, 2020)
In humans, Salmonella enterica infections are responsible for a plethora of medical conditions. These include intestinal inflammation and typhoid fever. The initial contact between Salmonella and polarized epithelial cells is established by the SPI4-encoded type I secretion system (T1SS), which secretes SiiE, a giant non-fimbrial adhesin. We have recombinantly produced various domains of this T1SS from Salmonella enterica serovar Typhimurium in Escherichia coli for further experimental characterization. We purified three variants of SiiD, the periplasmic adapter protein spanning the space between the inner and outer membrane, two variants of the SiiE N-terminal region and the N-terminal domain of the SiiF ATP-binding cassette (ABC) transporter. In all three proteins, at least one variant yielded high amounts of pure soluble protein. Secondary structure content and cooperative unfolding were investigated by circular dichroism (CD) spectroscopy. Secondary structure contents were in good agreement with estimates derived from SiiD and SiiF homology models or, in case of the SiiE N-terminal region, a secondary structure prediction. For one SiiD variant, protein crystals could be obtained that diffracted X-rays to approximately 4 Å resolution.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Protein expression; Purification; Salmonella; Type I secretion system (T1SS)